An innovative pendulum-type column-in-column (PCIC) system for structural vibration control induced by seismic ground excitations. (1st April 2022) - Fang, Xiaojun; Hao, Hong; Bi, Kaiming
Highlights: A novel pendulum-type column-in-column (PCIC) system is proposed to reduce seismic response of engineering structures. The optimum formulas of the system are derived using the classical 'fixed point' theory. Analytical and numerical studies are conducted to demonstrate the robustness and control effectiveness of the system. The proposed PCIC system can obviously control the vibrations of tall slender structures even if the PTMD deviates from the tuning conditions. Abstract: Recently, a sliding-type column-in-column (SCIC) system was proposed by the authors to reduce structural response using the TMD concept. The idea of the SCIC design is to split a column into an external and an internal column to form a nonconventional TMD system to control vibrations while not increasing the size nor compromising the load bearing ability of the column. It was found that the control effectiveness of this SCIC system became less effective when a large superstructure acting on the system. To overcome this drawback, the SCIC system is modified by converting the internal column into a pendulum TMD (PTMD) in this paper, i.e., forming a pendulum-type column-in-column (PCIC) system. To investigate the effectiveness of this novel system, the optimum design formulae of the system are firstly derived using the classical 'fixed point' theory. Sensitivity analyses are then carried out to validate the robustness of this system with respect to the superstructure mass, stiffness and damping of the PTMD. Nonlinear time history analyses are performed on the commercial software ABAQUS to demonstrate the control effectiveness. Both analytical and numerical results indicate that the proposed PCIC system shows a good robustness and performance in controlling seismic response of tall slender structures.